The development of innovation and ecological strategy of Poland and the European Union - Marciniuk-Kluska, Anna; Chrząścik, Ireneusz; Szymalska, Magdalena; Kluska, Mariusz (Studia Ecologiae et Bioethicae, 2008)
The paper presents the ecological strategy of the European Union and Poland as well as the aspects of the needs to implement innovations, the fast growth of the economy is influencing natural habitat more and more negatively. And at this stage new and more efficient technologies should be implemented and particularly eco-innovations. As the European Union directs more and more funds into this area, it becomes easier to receive financial aid. But the needs in this area are still enormous, they are particularly visible in those places where the danger zones for the natural habitat exist.